2017
DOI: 10.1016/j.jcin.2017.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Switching Dual Antiplatelet Therapy After Acute Coronary Syndrome According to On-Treatment Platelet Reactivity

Abstract: Switched DAPT was superior regardless of initial platelet reactivity but the benefit was greater in LTPR patients. Indeed, the switched strategy was highly effective in this group, which had impaired prognosis with unchanged DAPT but similar prognosis after switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…However, significant reductions in rehospitalization for unstable angina and revascularization were observed in the ticagrelor group. Unlike previous data, 8,10,13 our study showed that in patients with STEMI undergoing successful primary PCI, de-escalation was associated with a high incidence of secondary ischemic events as compared to ticagrelor, but with a low incidence as compared to clopidogrel. Our result supported the SCOPE registry, which has shown that de-escalation increased the rate of adverse cardiovascular events in the first month after hospital discharge.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…However, significant reductions in rehospitalization for unstable angina and revascularization were observed in the ticagrelor group. Unlike previous data, 8,10,13 our study showed that in patients with STEMI undergoing successful primary PCI, de-escalation was associated with a high incidence of secondary ischemic events as compared to ticagrelor, but with a low incidence as compared to clopidogrel. Our result supported the SCOPE registry, which has shown that de-escalation increased the rate of adverse cardiovascular events in the first month after hospital discharge.…”
Section: Discussioncontrasting
confidence: 97%
“…Although some previous studies have reported the safety of deescalation, the follow-up duration was short. 8,10,13 In 12 months follow-up, we found that as compared to clopidogrel, de-escalation did not increase the risk of bleeding events. Hence, de-escalation may be safe.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This effect was mostly driven by the 60% decrease in bleeding events in the switched group, without an increase in ischemic events. It is of note that the switched DAPT strategy was superior in terms of bleeding regardless of the initial platelet reactivity [73]. The recent TWILIGHT study further supported a strategy based on a shorter DAPT [74].…”
Section: Do Platelet Function Tests Help To Avoid Bleeding Events?mentioning
confidence: 85%
“…It is recognized that the efficacy of platelet inhibition due to antiplatelet therapy including novel potent P2Y12 inhibitors could be associated with a patient's BMI [8]. In other words, high or low BMI could lead to an inappropriate balance between anti-ischemic and bleeding risks [9][10][11]. Therefore, assessment of different antiplatelet strategies after PCI, stratified according to BMI, may provide additional insight into patients with a "high-risk" BMI.…”
Section: Introductionmentioning
confidence: 99%